36. STUDENT SATISFACTION WITH ONLINE AND FACE-TO-FACE LEARNING IN NURSING DURING THE NEW NORMAL IN THE ERA OF PANDEMIC COVID-19 (Vietnam Journal of Community Medicine, 2025)
Objective: Determine and compare the satisfaction levels of nursing students with online and face-to-face learning during the New Normal in The Era of Pandemic COVID-19.Methods: A cross-sectional study using a structured questionnaire assessed nursing students' opinions regarding their courses, including second and third-year students.Results: Students are delighted with face-to-face learning during the New Normal in the Era of the COVID-19 pandemic. Furthermore, they find this method more satisfactory than online learning, and the difference is statistically significant.Conclusions: Enhancing teaching methods and approaches is essential to improving the quality of training and effectively responding to future emergency epidemic situations.
Keywords: online learning; face-to-face learning; nursing students; students’ satisfaction